Humanitarian Assistance in 21 Century: Between Humanity and Sovereignty - Puspoayu, Elisabeth Septin; riyanto, sigit; Wattimena, Keanu Abinuno (Indonesia Law Reform Journal, 2023)
Humanitarian assistance is one of the actions that can be taken to limit and reduce the impact of armed conflict. Humanitarian assistance is aimed at civilians during armed conflicts. The purpose of this study is to analyze the position of humanitarian assistance in the 21st century. This research was conducted through conceptual and comparative approaches, as well as using normative legal research methods, also using prescription analysis techniques.  The results showed that the principle of distinction is the basic principle of humanitarian assistance, which means that this assistance is mandatory. State sovereignty must still be recognized and upheld in the context of providing humanitarian assistance. States have the primary responsibility to provide assistance to their peoples in the midst of armed conflict as one of the parties responsible for armed conflict, external humanitarian actors must respect the agreement and cooperation of States affected by armed conflict. Abstrak   Bantuan kemanusiaan merupakan salah satu Tindakan yang dapat dilakukan untuk membatasi dan mengurangi dampak dari adanya konflik bersenjata. Bantuan kemanusiaan ditujukan kepada masyarakat sipil selama konflik bersenjata. Tujuan dari penelitian ini untuk menganalisi kedudukan humanitarian assistance di abad 21. Penelitian ini dilakukan melalui pendekatan konseptual dan komparatif, serta  menggunakan metode penelitian hukum normatif, juga menggunakan teknik analisis preskripsi. Hasil penelitian menunjukan bahwa prinsip pembedaan adalah prinsip dasar bantuan kemanusiaan yang artinya bantuan ini merupakan hal yang wajib. Kedaulatan negara harus tetap diakui dan dijunjung tinggi dalam rangka pemberian bantuan kemanusiaan. Negara mempunyai tanggung jawab utama untuk memberikan bantuan kepada masyarakatnya yang sedang dilanda konflik bersenjata sebagai salah satu pihak yang bertanggung jawab pada konflik bersenjata, aktor kemanusiaan eksternal harus menghormati persetujuan dan kerja sama negara-negara yang terkena dampak dari konflik bersenjata